UPAYA MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI KEGIATAN COOKING CLASS UNTUK ANAK USIA 4-5 TAHUN DI PAUD PUTRI MUTIARA CERIA KOTA PEKANBARU - Indrawaty, Tri Putri; Zulkifli N, Zulkifli N; Novianti, Ria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack : This study aims to investigate the influence of activities Cooking Class for Kids fine motor skills. This study consists of two variables: fine motor and cooking class. The hypothesis proposed in this study are as follows: Through the implementation of this cooking class activities can improve fine motor skills of children aged 4-5 years in early childhood Cheerful Pearl Pekanbaru City